2016
DOI: 10.1152/ajplung.00251.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells inversely regulate airway inflammation in cigarette smoke-exposed mice

Abstract: The recruitment and activation of inflammatory cells into the respiratory system is considered a crucial feature in the pathophysiology of chronic obstructive pulmonary disease (COPD). Because dendritic cells (DCs) have a pivotal role in the onset and regulation of immune responses, we investigated the effect of modulating DC subsets on airway inflammation by acute cigarette smoke (CS) exposure. CS-exposed mice (5 days) were treated with fms-like tyrosine kinase 3 ligand (Flt3L) and 120g8 antibody to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In the current study, 1% ECVE significantly stimulated IL-6 secretion by LPS-matured DCs, suggesting E-cigarette use may promote an inflammatory environment in humans. However, the levels of other cytokines including IL-8, IL-10, IL-12 and TNF-α remained unchanged after ECVE treatment, although it has been reported that they are altered by CS treatment of DCs (Givi et al 2015(Givi et al , 2016Mortaz et al 2009;Vassallo et al 2005). It has also been reported that E-cigarette vapour condensate enhanced production of IL-6 by human alveolar macrophages (Scott et al 2018), consistent with our findings reported here for human DCs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, 1% ECVE significantly stimulated IL-6 secretion by LPS-matured DCs, suggesting E-cigarette use may promote an inflammatory environment in humans. However, the levels of other cytokines including IL-8, IL-10, IL-12 and TNF-α remained unchanged after ECVE treatment, although it has been reported that they are altered by CS treatment of DCs (Givi et al 2015(Givi et al , 2016Mortaz et al 2009;Vassallo et al 2005). It has also been reported that E-cigarette vapour condensate enhanced production of IL-6 by human alveolar macrophages (Scott et al 2018), consistent with our findings reported here for human DCs.…”
Section: Discussionsupporting
confidence: 91%
“…The effects of E-cigarettes on the human immune system are not fully elucidated; in particular, the effects of ECVE on human DCs have not been investigated previously although numerous studies have shown deleterious (and mainly immunosuppressive) effects of CS on DCs (Alkhattabi et al 2018;Arellano-Orden et al 2016;Givi et al 2016;Guinet et al 2004;Kroening et al 2008;Le Rouzic et al 2016;Liao et al 2015;Mortaz et al 2009;Guinet 2003, 2006;Nouri-Shirazi et al 2007;Robbins et al 2004Robbins et al , 2008Stampfli and Anderson 2009;Vassallo et al 2005). DCs are professional antigen presenting cells that link innate and adaptive immunity; therefore, due to the importance of DCs within the immune system, the aim of the present study was to investigate the effects of ECVE on the biological behaviour of DCs in vitro using human monocyte-derived DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Langerhans-type DCs have been observed selectively in small airways [ 105 ], whereas the numbers of bronchial mucosal DCs in the epithelium as well as the migratory CD83 + and CCR7 + DC subsets are reduced in patients with COPD [ 106 , 107 ]. The dysregulated localisation of these immune cells comes together with altered immune responses regulated by the different subsets [ 108 ]; cigarette smoke and the lung inflammatory milieu decrease lung myeloid DC maturation [ 109 , 110 ] and cause an imbalance to the costimulatory status of these cells [ 111 ]. In contrast, CD1c + DCs favour tolerogenic signalling and the induction of regulatory T cells [ 112 ].…”
Section: Chronic Obstructive Pulmonary Disease (Copd): Epidemiologmentioning
confidence: 99%
“…Mechanisms exist that perpetuate and amplify pulmonary inflammation in COPD lungs as chronic pulmonary inflammation often increases progressively as COPD severity increases and can persist after smoking cessation. Early studies focused on the activities of innate immune cells (25,26,31,62) and then CD8ϩ and CD4ϩ T cells in the pathogenesis of COPD (32,38,68). More recently, B cells have been linked to COPD as there are increases in the number and size of B cell-rich lymphoid follicles (LFs) in the severe stages of COPD and the presence of B cell products (autoantibodies) in COPD blood and lung samples (42,54,59).…”
mentioning
confidence: 99%